Comparative Analysis of In-Situ Left Internal Mammary Artery and Saphenous Vein Composite Grafts for Left Anterior Descending Artery Revascularization: A Propensity-Matched Study - Parth Bharat Solanki; Nivedita Vadodaria; Smit Bharat Solanki; Hitendra Kanzaria (Український журнал серцево-судинної хірургії)
Aim. This study aimed to evaluate the early and mid-term outcomes of a novel strategy using the in-situ left internal mammary artery (LIMA) with a great saphenous vein graft (SVG) to bypass the left anterior descending artery (LAD) in coronary artery bypass grafting (CABG).